Facile electrodeposition of biphasic CuSx/CoSx nanostructures as bifunctional electrocatalysts for seawater splitting - Mottakin M.; Selvanathan V.; Razali S.A.; Islam M.A.; Almohamadi H.; Alharthi N.H.; Yoshimura S.; Akhtaruzzaman M. (Elsevier Ltd, 2024)
Development of seawater splitting is essential for the sustainable hydrogen energy production via electrocatalysis. In this study, a facile electrodeposition technique is adopted to design a copper sulfide/cobalt sulfide biphasic composition on nickel foam as bifunctional electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). In saline water, bi-phasic CoSx/CuSx@NF catalyst provides the minimal overpotential of 230 mV at 10 mA cm?2 and 390 mV at 100 mA cm?2 for OER. The electrode exhibits the Tafel slope of 133.4 mV dec?1. CoSx/CuSx@NF catalyst also provides the minimal overpotential of 113 mV at 10 mA cm?2 for HER. From FESEM analysis, it was deduced that the interconnected nanosheet and nanoflower structure in CoSx/CuSx@NF provides high surface area and lowered interfacial resistance for improving OER and HER activity. The catalyst shows excellent multifunctional activity in urea oxidation reaction (UOR). The electrodes showed good stability in alkaline, chloride solutions by retaining its activity up to 24 h for OER and 60 hrs for HER. This study demonstrates a highly stable, reproducible, cost-effective electrodeposited biphasic catalyst for OER, HER, and UOR. 2023